A case report of tinea capitis in infant in first year of life - Narcisa Mandras; Janira Roana; Ornella Cervetti; Michele Panzone; Vivian Tullio (BMC, 2019)
Abstract Background Tinea capitis is a cutaneous fungal infection common among 3 to 7 year old children but it is rare in the first year of life. Case presentation We present a case of a 12-month-old infant with erythematous scalp lesions combined with hair loss. He was suspected of dermatophytosis and mycological analysis of all suspected lesions was performed. Clinical features and culture results confirmed tinea capitis caused by Microsporum canis. The infant patient was treated with griseofulvin for 2 months. However, 15 days later at the end of treatment he presented with a single vesicle positive for M. canis. Griseofulvin therapy continued for another month. After 3 months of follow-up, no recurrence was observed. Conclusions In infant, sometimes tinea capitis is misdiagnosed and underreported because it is similar to other scalp pathologies. Therefore, if erythematous scalp lesions are present, they must be examined from a mycological point of view to inform the differential diagnosis. Once diagnosed, treatment of tinea capitis can pose a dilemma because different factors may influence the choice between equally effective therapies (i.e. safety, age, formulation, cost). This case report suggests that it is important to establish an accurate diagnosis and  treatment for this dermatophytosis to avoid recurrences or therapeutic failures, especially in infants.